Gwaihir: Jupyter Notebook graphical user interface for Bragg coherent diffraction imaging. Issue 4 (16th July 2022) - Simonne, David; Carnis, Jérôme; Atlan, Clément; Chatelier, Corentin; Favre-Nicolin, Vincent; Dupraz, Maxime; Leake, Steven J.; Zatterin, Edoardo; Resta, Andrea; Coati, Alessandro; Richard, Marie-Ingrid
Abstract : In a world where data are steadily made more available, Gwaihir is a tool that overcomes multiple issues by bridging remote access, cluster computing and a user‐friendly interface, consequentially improving the link between synchrotrons and their users for Bragg coherent diffraction imaging. Abstract : Bragg coherent X‐ray diffraction is a nondestructive method for probing material structure in three dimensions at the nanoscale, with unprecedented resolution in displacement and strain fields. This work presents Gwaihir, a user‐friendly and open‐source tool to process and analyze Bragg coherent X‐ray diffraction data. It integrates the functionalities of the existing packages bcdi and PyNX in the same toolbox, creating a natural workflow and promoting data reproducibility. Its graphical interface, based on Jupyter Notebook widgets, combines an interactive approach for data analysis with a powerful environment designed to link large‐scale facilities and scientists.